Mechanical Properties and Durability of Impregnated Sengon Wood Using Monoethylene Glycol and SiO2 Nanoparticles - Rahayu, Istie; Riadhi, Mohamad Rizki; Wahyuningtyas, Irma; Prihatini, Esti; Ismail, Rohmat (Talenta Publisher, 2024)
Sengon wood (Falcataria moluccana Miq.) is a short-rotation wood which has weak quality characteristics, i.e., low specific gravity, strength, durability, density, and dimensional stability. This study aimed to find out the impact of monoethylene glycol (MEG) and SiO2 nanoparticle impregnation treatment on mechanical properties (MOE, MOR, and hardness) and wood durability. Four kinds of solution were used to impregnate sengon wood: untreated (water), 50% MEG, MEGSiO2 0.5%, and MEGSiO2 1%. The impregnation process was initiated by applying 0.5 atm of vacuum for 60 minutes, followed by 2.5 bar of pressure for 120 minutes. The results showed that MEG and SiO2 nanoparticle impregnation treatment significantly affected the mechanical properties (MOE, MOR, and hardness) and the durability of sengon wood against dry wood and subterranean termite bites. The optimum treatment to increase the properties of sengon wood so that its strength class increases to III-IV and durability class IV was MEG SiO2 1% treatment